The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1530/eje.0.1320302
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous computed tomography-guided ethanol injection in aldosterone-producing adrenocortical adenoma

Abstract: The feasibility, safety and effectiveness of percutaneous computed tomography-guided ethanol injection (PEI-CT) was investigated in a patient affected by aldosterone-producing adenoma (APA). A 42-year-old male patient with typical features of hyperaldosteronism presented a solitary left adrenal adenoma measuring 2 cm, with a normal contralateral gland, evidenced by both CT scan and adrenal [75Se-19]-nor-cholesterol scintigraphy. After normalization of potassium plasma levels, 4 ml of sterile 95% ethanol with 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Recently PEI has also been employed for the treatment of endocrine tumors of the thyroid and parathyroid [3][4][5] . In addition, the use of a high concentration of acetic acid, instead of ethanol, has achieved safer and more effective results [6][7] With respect to percutaneous injection therapy for adrenocortical solid tumors, however, only 1 case with aldosterone-producing adenoma (APA) has ever been reported to be successfully treated by PEI in spite of associated massive leakage [8]. Here we present 3 cases with APA who have undergone computed tomography(CT)-guided percutaneous acetic acid injection (PAT) therapy.…”
mentioning
confidence: 99%
“…Recently PEI has also been employed for the treatment of endocrine tumors of the thyroid and parathyroid [3][4][5] . In addition, the use of a high concentration of acetic acid, instead of ethanol, has achieved safer and more effective results [6][7] With respect to percutaneous injection therapy for adrenocortical solid tumors, however, only 1 case with aldosterone-producing adenoma (APA) has ever been reported to be successfully treated by PEI in spite of associated massive leakage [8]. Here we present 3 cases with APA who have undergone computed tomography(CT)-guided percutaneous acetic acid injection (PAT) therapy.…”
mentioning
confidence: 99%
“…5 PEI has been widely used in small hepatocellular carcinoma (HCC), and the survival rates of surgical resection and PEI are comparable. 6 The application of PEI in nodular lesion of endocrine glands, including thyroid, parathyroid, and adrenal glands, has also been proposed. 6 A retrospective study evaluated the effectiveness of CT-guided percutaneous chemical ablation of adrenal neoplasms under CT guidance.…”
Section: Discussionmentioning
confidence: 99%
“…6 The application of PEI in nodular lesion of endocrine glands, including thyroid, parathyroid, and adrenal glands, has also been proposed. 6 A retrospective study evaluated the effectiveness of CT-guided percutaneous chemical ablation of adrenal neoplasms under CT guidance. 7 Of the seven patients with PA, all reached the normal range of serum potassium level, PAC, Figure 1 The computed tomography scan revealed a hypodense tumor at the right adrenal gland (arrow) 4 years after the first percutaneous ethanol injection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Ultrasound-guided ethanol injection has been used in the treatment of a variety of solid and cystic masses, such as renal, splenic, hepatic, and thyroid cysts. [7][8][9][10][11][12] Important advantages of this technique are its low cost and few adverse effects. Ultrasound-guided ethanol injection was first used to treat gynecologic conditions in 1988; since then, many investigators have reported favorable results for ablation of ovarian tumors.…”
mentioning
confidence: 99%